Examining Employee Intention in Paying Professional Zakat: A Model of Zakat Knowledge, Altruism, Transparency, and Trust - Rana Nabila Ramadanis; Diamantin Rohadatul Aisy; Prilla Kurnia Ningsih (Universitas Alma Ata, 2026)
Purpose: This study examines the factors influencing employees’ intention to pay professional zakat in the Jakarta area. Although the potential of professional zakat in Indonesia is substantial, its collection remains low due to limited public understanding and participation. Methodology: This research uses a quantitative approach with data collected from 120 employees through a structured questionnaire. Multiple linear regression analysis was conducted using SPSS version 26 to test the influence of zakat knowledge, altruism, transparency, and trust on payment intention. Results: The findings reveal that zakat knowledge, altruism, and trust significantly influence the intention to pay professional zakat, while transparency has no significant effect. These results highlight the importance of cognitive and trust-related factors in shaping payment intention. Conclusion: Strengthening zakat literacy and building trust in zakat institutions are essential strategies to enhance professional zakat participation. The study underscores that internal understanding and trust are stronger predictors than perceived transparency. Implications: The limited sample size and focus on the Jakarta area may restrict the generalizability of the findings. Future research should expand the scope and consider broader populations to validate the results. Originality: This study offers originality by simultaneously analyzing zakat knowledge, altruism, transparency, and trust within a single empirical model. It provides a more comprehensive perspective compared to prior studies that examined these variables separately.